ANALISIS PERBEDAAN TERAPI DISMENORHEA DENGAN METODE EFFLERUAGE, KNEADING, DAN YOGA DALAM MENGATASI DISMENORHEA - Akademi Kebidanan YLPP Purwokerto, Sugi Purwanti (Jurnal Kebidanan)
<!–[if gte mso 9]> Normal 0 false false false IN X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> ANALISIS PERBEDAAN TERAPI DISMENORHEA DENGAN METODE EFFLERUAGE, KNEADING, DAN YOGA DALAM MENGATASI DISMENORHEA Sugi Purwanti Akademi Kebidanan YLPP Purwokerto ABSTRACT Dysmenorrhea is pain in the lower abdomen felt during menstruation. Dysmenorrhea is the most frequent symptom complained. These disorders are subjective, difficult to assess the weight and intensity. The Effleurage, kneading, yoga are method that used to solve dysmenorrhea. The purpose of this research is to knowing comparative efectiveness of effleurage, kneading and yoga method to decrease the intensity of dysmenorrhea. The research was quasy experimental design with pre test and post test design. Respondent was student YLPPâ€™s academy of midwivery, numbered 45 people by random sampling. The research was using a paired sample T test with value of Î± 0.05. The average dysmenorrheal intensity before doing effleurage, kneading, yoga are 5,27 : 6,27 : 6,27. The average dysmenorrheal intensity after doing effleurage, kneading, yoga are 3.00 : 2,87 : 3,47. The average differences before and after effleurage, kneading, yoga are 2,267 : 3,400 : 2,800 with p value 0,000. The size effect of effleurage, kneading, yoga to decrease dismenorrhea intensity are 0,875 : 0,968 : 0,923. There are a significant difference before and after doing therapy effleurage, kneading and yoga. The effleurage therapy, kneading therapy, and yoga treatment can be used as the alternative intervention to decrease dismenorrhea intensity. Keyword : Dysmenorrhea, effleurage, kneading, yoga <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>